2013
DOI: 10.1186/1471-2369-14-87
|View full text |Cite
|
Sign up to set email alerts
|

U-shaped association between central body fat and the urinary albumin-to-creatinine ratio and microalbuminuria

Abstract: BackgroundThe prevalence of obese and overweight patients has increased dramatically worldwide. Both are common risk factors for chronic kidney disease (CKD) as indicated by a diminished estimated glomerular filtration rate (eGFR) or microalbuminuria. This study aimed to investigate whether anthropometric parameters [waist circumference (WC), waist-to-height ratio (WHtR) and body mass index (BMI)] are associated with renal function in a population-based study of Caucasian subjects.MethodsData from 3749 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
2
23
1
1
Order By: Relevance
“…have reported that increasing BMI is associated with a risk of albumin‐to‐creatinine ratio progression. A study with 3,749 participants (BMI 22.8–30.2 kg/m 2 ) from the Study of Health in Pomerania showed that low BMI is positively correlated with the urinary albumin‐to‐creatinine ratio. Yet, in the present study, it was determined that a higher BMI was positively correlated with DKD.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…have reported that increasing BMI is associated with a risk of albumin‐to‐creatinine ratio progression. A study with 3,749 participants (BMI 22.8–30.2 kg/m 2 ) from the Study of Health in Pomerania showed that low BMI is positively correlated with the urinary albumin‐to‐creatinine ratio. Yet, in the present study, it was determined that a higher BMI was positively correlated with DKD.…”
Section: Discussioncontrasting
confidence: 72%
“…The major strength of the present study was the comprehensively discussed relationship between BMI and diabetic macrovascular and microvascular complications. We demonstrated that BMI showed a U‐shaped association with DPN and PAD, whereas the results of the aforementioned studies showed a linear relationship. The observed differences could result from methodological differences, differences in the definitions of vascular complications, inadequate clinical sample sizes and differences in study participants (e.g., some studies did not include the lean population, some studies only examined the elderly population).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…18 A recent study evaluating the associations between WC, WHtR, BMI and renal function also demonstrated that both obese and very thin subjects have a higher risk of renal impairment. 19 BMI and WC were found to be associated with reduced estimated GFR (eGFR) in Japanese cohort studies. 20,21 Central obesity was positively related to WC in some cross-sectional studies, including Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Показано наличие U-образной связи между маркерами центрального ожирения и соотношени-ем альбумин/креатинин в моче, а также микроаль-буминурией в общей популяции, что свидетельст-вует о том, что как люди с ожирением, так и очень худые люди имеют повышенный риск почечной недостаточности [58]. У здоровых людей среднего возраста снижение чувствительности к инсулину и гиперинсулинемия также являются факторами рис-ка альбуминурии [61].…”
Section: огляд літературиunclassified